2020
DOI: 10.23932/2542-0240-2019-12-5-145-159
|View full text |Cite
|
Sign up to set email alerts
|

Polar Views on the Arctic: Arctic Policies of Russia and Circumpolar Countries

Abstract: The article discusses current issues of Arctic governance. The main motives of the growing interest of the world community to this region are revealed. Comparative analysis of the conceptual framework and key priorities of the Arctic policy of the Russian Federation and other circumpolar powers based on a study of their national Arctic strategies. It was determined that the main difference between the Russian model of managing the Arctic zone lies in the priority of exploitation of natural resources on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…[92]. Several studies attempted to assess sustainability of resource exploration in the Arctic in terms of environmental aspects, such as the rational use of mineral resources, ensuring a high level of energy and resource efficiency, reducing the environmental impact, and preserving fragile ecosystems [93]. Gassiy et al concluded that the SD of the Arctic systems is determined by a balance between the interests of key Nowadays, companies' and projects' management is faced with the necessity to strike a balance between operational effectiveness and strategic thinking on the sustainability issue [88]; in our opinion, this is the cornerstone for the achievement of strategic sustainability.…”
Section: Efficiency/sustainability Assessment Of Arctic Oil and Gas P...mentioning
confidence: 99%
See 1 more Smart Citation
“…[92]. Several studies attempted to assess sustainability of resource exploration in the Arctic in terms of environmental aspects, such as the rational use of mineral resources, ensuring a high level of energy and resource efficiency, reducing the environmental impact, and preserving fragile ecosystems [93]. Gassiy et al concluded that the SD of the Arctic systems is determined by a balance between the interests of key Nowadays, companies' and projects' management is faced with the necessity to strike a balance between operational effectiveness and strategic thinking on the sustainability issue [88]; in our opinion, this is the cornerstone for the achievement of strategic sustainability.…”
Section: Efficiency/sustainability Assessment Of Arctic Oil and Gas P...mentioning
confidence: 99%
“…[92]. Several studies attempted to assess sustainability of resource exploration in the Arctic in terms of environmental aspects, such as the rational use of mineral resources, ensuring a high level of energy and resource efficiency, reducing the environmental impact, and preserving fragile ecosystems [93]. Gassiy et al concluded that the SD of the Arctic systems is determined by a balance between the interests of key stakeholders-the state, business, science, society, etc.…”
Section: Efficiency/sustainability Assessment Of Arctic Oil and Gas P...mentioning
confidence: 99%
“…В России основными потребителями инвестиций выступают регионы, среди которых ведущую роль для развития на-циональной экономики играют регионы Арктической зоны Российской Федерации (АЗРФ). Здесь по прогнозным оценкам сосредоточено свыше 90 % общероссийских запасов алмазов, золота (40 %), хрома и марганца (90 %), апатита (50 %), вермикулита (100 %), платиновых металлов, угля, никеля, кобальта, олова, вольфрама, ртути и других важнейших полезных ископаемых [5], а также более 270 млрд т у.т., включая около 48,5 млрд т нефти и конденсата и свыше 220 трлн м 3 природного газа [6]. Благодаря ECONOMIC SCIENCES (08.00.05, 08.00.10, 08.00.13, 08.00.14)…”
unclassified